Quantitative ultrastructural characteristics of the mitochondria network of ventricular muscle cells during prenatal ontogeny under the chronic hypoxia - M. V. Ivanchenko (Zaporozhye State Medical University, 2013)
We have studied a quantitative ultrastructural analysis of the formation and reactions of the mitochondria network in rat muscle cells during prenatal ontogeny under the chronic hypoxia in the experiment. Analysis showed that chronic hypoxia leads to delayed rate of growth and development of the mitochondria heterogeneity. Changes of the parameters are different in the heart parts and depend upon the layer of myocardium.